(3EOGQI GdehGLgIs - (3QhHQJ(B, (3eGjQs ((3GdLjRI(B:s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B,s, 2006)
(3jVe GdJMce GdJGe aj GdeTGYQ hGdEfaYGdGJ, GdhUhd Edi fbWI GJaGb, GdeUOGbjI hGddeSGJ GdEfSGfjI ddhUhd dfbWI GJaGb, SHd GbfGY GdWQa GdBNQ, fMh NWGH LOdj eMce UYH GdJfajP, PNjQJc ef GdcdeGJ hGdYHGQGJ GdeDKQI efWbjG, GdYdGbI Hjf GdEMJjGLGJ GdYWajI hGdNWGH GdLOdj, SHd EOGQI GdYbHGJ hGdCReGJ, UjGZI GdNWGH GdLOdj GdTagj, YQV GdNWGH GdLOdj Hjf CQhbI GdELJeGYGJs
Keywords: (3GdEOGQI(B- (3GdYdGbGJ GdELJeGYjIs; (3Mb GdELJeGYs